Canine smooth muscle tumors: A clinicopathological study. Issue 2 (March 2022) - Avallone, Giancarlo; Pellegrino, Valeria; Muscatello, Luisa Vera; Roccabianca, Paola; Castellani, Gastone; Sala, Claudia; Tecilla, Marco; Valenti, Paola; Sarli, Giuseppe
Canine smooth muscle tumors (SMTs) commonly develop in the alimentary and female genital tracts and less frequently in soft tissue. The definition of histological criteria of malignancy is less detailed for SMTs in dogs than in humans. This study evaluated the clinicopathologic features of canine SMTs and compared the veterinary and human medical criteria of malignancy. A total of 105 canine SMTs were evaluated histologically and classified according to both veterinary and human criteria. The Ki67 labeling index was assessed in all SMTs. Estrogen receptor (ER) and progesterone receptor (PR) expression was evaluated for soft tissue SMTs. Follow-up data were available in 25 cases. SMTs were diagnosed in the female genital tract (42%), alimentary tract (22%), and soft tissue (20%). Soft tissue SMTs frequently arose in the perigenital area, pelvic cavity, and retroperitoneum. A subset of soft tissue SMTs expressed ER and/or PR, resembling the gynecologic type of soft tissue SMT in humans. SMTs were less frequently malignant when assessed with human criteria than with veterinary criteria, better reflecting their benign behavior, especially in the genital tract where human criteria tolerate a higher mitotic count for leiomyoma. Decreased differentiation was correlated with increased proliferation, necrosis, and reduced desmin expression. Mitotic count, Ki67 labeling index, and necrosis were correlated with metastases and tumor-related death. Further prognostic studies are warranted to confirm the better performance of the human criteria when assessing SMT malignancy, especially genital cases, to confirm their usefulness in ER/PR-expressing soft tissue SMTs, and to better define the most useful prognostic parameters for canine SMTs.